Bimetallic MOF derived nickel nanoclusters supported by nitrogen-doped carbon for efficient electrocatalytic CO₂ reduction - Wang, Haojing (2022)
Utilizing electrocatalytic CO2 reduction (ECR) to decrease the carbon footprint has been regarded as a promising pathway. Herein, we report the synthesis of Ni nanoclusters (NCs) of below 2 nm highly dispersed on N-doped carbon using a Ni/Zn bimetallic metal-organic framework (MOF) precursor. The size and the content of the Ni catalyst can be effectively controlled by varying the Ni:Zn ratio in MOF precursors. The −NH2 group in MOF ligand critically influences the size of Ni catalyst, as well as the property of the carbon substrate. At the optimum ratio of 1:150, Ni NCs with an average size of 1.9 nm anchored on pyridinic N-rich carbon were obtained after MOF pyrolysis. The resultant catalyst exhibits a high Faradaic efficiency for CO (FECO, 98.7%) and considerable partial current density for CO (JCO, −40.4 mA·cm−2) at −0.88 V versus reversible hydrogen electrode (RHE). Benefiting from the synergistic effect of small Ni clusters and their optimal interaction with the carbon support, the catalyst displays exceptional long-term stability. Density functional theory (DFT) calculations carried out for the three model structures confirm that Ni NCs anchored on N-doped carbon facilitate the easier formation of *COOH intermediate and faster electron transfer rate compared with the large-sized Ni particles represented by Ni(111) and the N-doped carbon without Ni.